Molecular epidemiology of avian influenza virus and Newcastle disease virus in West and Central Africa and in Luxembourg - (:unkn) unknown (My University, 2012)
Poultry meat and eggs constitute one of the cheap sources of protein around the world but poultry production is threatened by two main viral diseases, highly pathogenic avian influenza and Newcastle disease, with economic and public health implications worldwide. The introduction of highly pathogenic avian influenza H5N1 virus in Africa in 2006 highlighted the necessity of a better understanding of avian influenza virus (AIV) in Africa. Through surveillance studies, we found that H5N1 virus was not circulating anymore in sub-Saharan Africa after 2008. However, phylogenetic analyses performed on the genome of low pathogenic H5N2 viruses found in wild birds in Nigeria revealed that they were reassortants. The similarity of one gene to those found in other AIV viruses from Southern Africa strengthened the hypothesis that AIV may actually persist and circulate in Africa. We have shown that new virulent strains of Newcastle disease virus (NDV) constituted the majority of the strains detected. Their genetic distance compared to other NDV strains, their genetic diversity and their geographic dispersion in West and Central Africa suggested that these strains probably evolved locally, that they circulated for some time in the region and that trade and movement of animals likely contributed to their spread. Our findings also suggested that the contribution of wild birds to the dispersion of virulent strains of NDV was probably limited. In Luxembourg however, wild birds may be an important player for the introduction of NDV strains
Keywords: African Research